Effect of Dielectric Properties of a Solvent-Water Mixture Used in Microwave-Assisted Extraction of Antioxidants from Potato Peels - Ashutosh Singh; Gopu Raveendran Nair; Pansa Liplap; Yvan Gariepy; Valerie Orsat; Vijaya Raghavan (MDPI AG, 2014)
The dielectric properties of a methanol-water mixture were measured at different temperatures from 20 to 80 °C at two frequencies 915 MHz and 2450 MHz. These frequencies are most commonly used on industrial and domestic scales respectively. In this study, the dielectric properties of a methanol-water mixture were found to be dependent on temperature, solvent concentration, and presence of plant matrix. Linear and quadratic equations were developed to establish the dependency between factors. At 2450 MHz, the dielectric constant of methanol-water mixtures was significantly affected by concentration of methanol rather than by temperature, whereas the dielectric loss factor was significantly affected by temperature rather than by methanol concentration. Introduction of potato peel led to an increase in the effect of temperature on the dielectric properties of the methanol fractions. At 915 MHz, both the dielectric properties were significantly affected by the increase in temperature and solvent concentration, while the presence of potato peel had no significant effect on the dielectric properties. Statistical analysis of the dissipation factor at 915 and 2450 MHz revealed that both temperature and solvent concentration had a significant effect on it, whereas introduction of potato peels at 915 MHz reduced the effect of temperature as compared to 2450 MHz. The total phenolic yield of the microwave-assisted extraction process was significantly affected by the solvent concentration, the dissipation factor of the methanol-water mixture and the extraction time.